THE DEVELOPMENT OF CIVIL LAW PROCEDURES IN THE RESOLUTION OF DIVORCE DISPUTES IN THE RELIGIOUS COURT - Halim, Abdul (Legal Standing : Jurnal Ilmu Hukum, 2019)
Relations which appear from legal actions do not always end well. It is not seldom that it may end with conflicts or disputes which end in court. To demand for the rights which appear from those legal relations, there needs to be some procedures and regulations so that the demand of rights may be carried out according to the law. The law which regulates those things are usually called the civil law procedures. The resolution of civil disputes in court (litigation) and the resolution of civil disputes through a non-court manner (non-litigation) in the context of the divorce dispute resolution in the Religious Court, is a combination between the litigation and the nonlitigation mmethods. This is rather interesting to be studied. The interesting part is its effectivity as a preventive or a repressive effort in handling the divorce cases in the Religious Court.